The impact of local economic development through SMMEs on Seshego Industrial Site, Zone six (6) - Mohapi, Monare Mahlomola (My University, 2005)
Refer to document
Thesis (M. Dev.) -- University of Limpopo, 2005
Keywords: Local economic development; Small, Medium and Micro-Enterprises; Small business -- South Africa; Entrepreneurship -- South Africa -- Limpopo Province